Consolidated Health Economic Evaluation Reporting Standards (CHEERS) statement. (June 2013) - Husereau, Don; Drummond, Michael; Petrou, Stavros; Carswell, Chris; Moher, David; Greenberg, Dan; Augustovski, Federico; Briggs, Andrew H.; Mauskopf, Josephine; ,
Abstract Economic evaluations of health interventions pose a particular challenge for reporting. There is also a need to consolidate and update existing guidelines and promote their use in a user-friendly manner. The Consolidated Health Economic Evaluation Reporting Standards (CHEERS) statement is an attempt to consolidate and update previous health economic evaluation guidelines efforts into one current, useful reporting guidance. The primary audiences for the CHEERS statement are researchers reporting economic evaluations and the editors and peer reviewers assessing them for publication. The need for new reporting guidance was identified by a survey of medical editors. A list of possible items based on a systematic review was created. A two round, modified Delphi panel consisting of representatives from academia, clinical practice, industry, government, and the editorial community was conducted. Out of 44 candidate items, 24 items and accompanying recommendations were developed. The recommendations are contained in a user-friendly, 24-item checklist. A copy of the statement, accompanying checklist, and this report can be found on the ISPOR Health Economic Evaluations Publication Guidelines Task Force website (www.ispor.org/TaskForces/EconomicPubGuidelines.asp). The hope is that CHEERS will lead to better reporting and, ultimately, better health decisions. To facilitate dissemination and uptake, the CHEERS statement is being co-published across 10 health economics and medical journals. Other journals and groups are encouraged to endorse CHEERS. The author team plans to review the checklist for an update in 5 years.